Analysis of Factors Affecting Poverty in Maluku Province 2011-2022 - Siregar, Vina Estetica; Benardin, Benardin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the effect of Capital Expenditure, Regional Original Revenue (PAD), Population, and Products Gross Regional Domestic Product (GRDP) to poverty rates in regions and cities in Maluku Province during 2011-2022. This research utilizes secondary data sourced from the Directorate General of Fiscal Balance Finance of the Republic of Indonesia and the Central Bureau of Statistics. The analysis method applied in this research is panel data regression analysis. The results of this study indicate that PAD, population, and GRDP have a significantly negative effect on poverty. On the other hand, capital expenditure has a positive effect on poverty, but it is not statistically significant.